A secure and efficient way of node membership verification in wireless sensor networks - Pathan, Al-Sakib Khan; Hong, Choong Seon (2007)
This paper proposes an efficient mechanism of node membership verification within the groups of sensors in a wireless sensor network (WSN). We utilize one-way accumulator to check the memberships of the legitimate nodes in a secure way. Our scheme also supports the addition and deletion of nodes in the groups in the network. Our analysis shows that, our scheme could be well-suited for the resource constrained sensors in a sensor network and it provides a lightweight mechanism for secure node membership verification in WSN.